Effect of biophysical conditions on standing and soil carbon storage in various land uses in Gunung Mas, Central Kalimantan, Indonesia - PENZA LINDIANI; LETI SUNDAWATI; UJANG SUWARNA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lindiani P, Sundawati L, Suwarna U. 2023. Effect of biophysical conditions on standing and soil carbon storage in various land uses in Gunung Mas, Central Kalimantan, Indonesia. Biodiversitas 24: 4493-4502. One of the human activities that accelerates climate change is degradation and deforestation, which can lead to new land use in the form of palm oil plantations and agroforestry. Both of these land uses have the potential to store carbon, which can be optimized if the influencing factors are known. This study aims to estimate the potential for carbon storage in palm oil and agroforestry plantations in Gunung Mas, Central Kalimantan, Indonesia, and to analyze the effect of biophysical conditions such as topography, soil fertility, and stand density on the potential for carbon storage. The research was conducted in palm oil plantations (POP) and agroforestry areas categorized as agroforestry with forestry and palm oil plantation commodities (AG-SS), as well as agroforestry consisting of forestry, palm oil, and fruit crops (AG-SSB). Sample plots were determined through purposive sampling with 30 plots for each land use. The research results show significant differences in aboveground carbon (AGC), soil organic carbon (SOC), and total carbon storage among the three land uses. The largest total AGC was in AG-SS (66.24 ton.ha-1), while the lowest AGC was observed in POP (48.15 ton.ha-1). The greatest SOC was recorded in AG-SSB (2163.21 ton. ha-1), followed by POP (1922.12 ton.ha-1) and AG-SS (1846.72 ton.ha-1). The highest total carbon storage was measured in AG-SSB (2223.36 ton.ha-1), followed by POP (1970.27 ton.ha-1), and the lowest in AG-SS (1912.96 ton.ha-1). Biophysical factors, including topography, soil fertility, and stand density, influenced carbon storage in each land use. Topography and stand density factors significantly influenced AGC, while soil fertility factors significantly affected SOC and total carbon storage in all three land uses.